The Frequency of Hypertension and Micro-Albuminuria in Diabetic Patients with Retinopathy - Fakhar uz Zaman, Imran Khuwaja, Basharat Sami, Muhammad Ahmad, (Pakistan Journal of Medical & Health Sciences, 2022)
The developed world is facing a lot of health problems; among them, one of the major ones is Diabetes Mellitus. In Pakistan, this problem has been increasing consistently due to a plethora of reasons. The current figures of people suffering from Diabetes in Pakistan stand at 7 million and this number has shown colossal growth by the day. Study Design: A cross-sectional study was performed on 131 patients from January 2017 to August 2017 on all diabetic patients diagnosed already for 5 years or more in the medicine wards of Ayub Teaching Hospital, Abbottabad. Their fasting blood sugar, random blood sugar, and 24-hour urine for protein analysis were measured in addition to recording their blood pressure for the purpose of identification of hypertensive patients. All patients were screened for diabetic retinopathy using a Welch Allyn Fundoscope. Results: Out of these 131 patients, Hypertension and microalbuminuria were present in 51.9% and 47.3% patients respectively. Diabetic retinopathy was found in 39.7% of study participants. It was evident that microalbuminuria and hypertension are directly related to diabetic retinopathy (p < 0.05), It greatly influences it on major levels. Microalbuminuria was associated with the age of the study participants (p = 0.05). Conclusion: This study showed that hypertension and microalbuminuria were significantly associated with the development of diabetic retinopathy.